2019
DOI: 10.1177/0145561319862216
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Stapedotomy: Overcoming Limitations of Operating Microscope

Abstract: The study is aimed to assess the scope of endoscopic stapedotomy in overcoming technical challenges faced during conventional stapedotomy using operating microscope. Sixty-four patients with clinical and audiological diagnosis of otosclerosis were randomly assigned into one of the 2 groups—one underwent conventional stapedotomy using operating microscope, while the other group underwent endoscopic stapedotomy, the operating surgeon being the same for both groups, for all cases. The 2 groups were observed in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 20 publications
0
42
1
7
Order By: Relevance
“…At the first follow-up in this study, 5 patients (16.66%) reported various degrees of taste dysfunction, and at 24 weeks, the number decreased to 2 (6.66%). Preservation of taste sensation in our study was significantly better than that reported in the literature, where 65.62% of patients had various degrees of taste dysfunction postoperatively ( Das et al., 2019 ). This encouraging result may be partially related to the transient nature of the taste disorder, which usually recovers within six months of surgery ( Yung et al., 2008 ; Guder et al., 2012 ; Berling Holm et al., 2017 ), as demonstrated in the present study.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…At the first follow-up in this study, 5 patients (16.66%) reported various degrees of taste dysfunction, and at 24 weeks, the number decreased to 2 (6.66%). Preservation of taste sensation in our study was significantly better than that reported in the literature, where 65.62% of patients had various degrees of taste dysfunction postoperatively ( Das et al., 2019 ). This encouraging result may be partially related to the transient nature of the taste disorder, which usually recovers within six months of surgery ( Yung et al., 2008 ; Guder et al., 2012 ; Berling Holm et al., 2017 ), as demonstrated in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…In the present study, the chorda tympani nerve was transposed in 11 patients (36.66%) and resected in 1 patient (3.33%) because of overstretching during surgery. As described by Das et al., 81.25% of the patients who underwent endoscopic stapes surgery required transposition of the chorda tympani nerve ( Das et al., 2019 ). The better preservation of the nerve in the present study may be due to the wide-angle view of the endoscope, requiring minimal displacement of the chorda tympani nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The domain of transcanal endoscopic ear surgery has been expanding ever since, with surgeries addressing diseases involving external ear to as far as the lateral skull base. [1][2][3] The main reasons behind this are the technical advantages that endoscopes offer in comparison to conventional microscopes, such as a wider field of vision, higher magnification to see finer structural details and the ability to look around corners without disrupting normal tissues for the sake of access. 4 Although endoscopes have established a firm ground in otological surgery, there are legitimate concerns regarding their safety.…”
Section: Introductionmentioning
confidence: 99%
“…6 Stapedotomy is a safe effective procedure with 95% hearing restoration results reported. 2,4,7 Traditionally stapes surgery has been done using a microscope. Endoscopes were introduced in middle ear surgery in 1990's by Dr Muaaz Tarabichi, reported that endoscopic stapes surgery in 12 cases with 87% patients reporting audiological improvement.…”
Section: Discussionmentioning
confidence: 99%
“…3 Endoscopes have evolved as a tool of safe and effective surgery in otological practice and surpass the microscope in middle ear procedures owing to better visualization of anatomy in the middle ear. 4 Stapes surgery is no different and is increasingly being performed with endoscopes. We share our experience if 45 cases of total endoscopic stapes surgery.…”
Section: Introductionmentioning
confidence: 99%